Combination of immune checkpoint inhibitors with radiation therapy in cancer: A hammer breaking the wall of resistance - Voronova, Veronika; Vislobokova, Anastasia; Mutig, Kerim; Samsonov, Mikhail; Peskov, Kirill; Sekacheva, Marina; Materenchuk, Maria; Bunyatyan, Natalya; Lebedeva, Svetlana (Frontiers in Oncology, 2022)
Immuno-oncology is an emerging field in the treatment of oncological diseases, that is based on recruitment of the host immune system to attack the tumor. Radiation exposure may help to unlock the potential of the immune activating agents by enhancing the antigen release and presentation, attraction of immunocompetent cells to the inflammation site, and eliminating the tumor cells by phagocytosis, thereby leading to an overall enhancement of the immune response. Numerous preclinical studies in mouse models of glioma, murine melanoma, extracranial cancer, or colorectal cancer have contributed to determination of the optimal radiotherapy fractionation, as well as the radio- and immunotherapy sequencing strategies for maximizing the antitumor activity of the treatment regimen. At the same time, efficacy of combined radio- and immunotherapy has been actively investigated in clinical trials of metastatic melanoma, non-small-cell lung cancer, and renal cell carcinoma. The present review summarizes the current advancements and challenges related to the aforementioned treatment approach.